Analisis Sosio-Empiris Terhadap Kesadaran Hukum Pengguna Aplikasi Paylater di Kalangan Mahasiswa Universitas Pertiba - Septiadi Septiadi; Eko Riyadi; Sri Yuliana (Jurnal Hukum Lex Generalis, 2025)
This study analyzes the legal awareness of Pertiba University students who use Paylater applications through a socio-empirical approach. Questionnaire results show that 45.8% of students have used Paylater, mainly Shopee PayLater. Their legal awareness is considered adequate, yet still low in reading terms and conditions and understanding legal protection mechanisms. Students recognize risks such as penalties and data misuse, but their knowledge of dispute resolution remains limited. The study highlights the need to improve digital legal literacy among Paylater service users.